2015
DOI: 10.1098/rspb.2015.1549
|View full text |Cite
|
Sign up to set email alerts
|

In a warmer Arctic, mosquitoes avoid increased mortality from predators by growing faster

Abstract: Climate change is altering environmental temperature, a factor that influences ectothermic organisms by controlling rates of physiological processes. Demographic effects of warming, however, are determined by the expression of these physiological effects through predator -prey and other species interactions. Using field observations and controlled experiments, we measured how increasing temperatures in the Arctic affected development rates and mortality rates (from predation) of immature Arctic mosquitoes in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 56 publications
(94 reference statements)
3
113
0
1
Order By: Relevance
“…Previous studies showed that acclimation to low temperatures forms microbial communities that are not only sturdier but also perform better when at warmer temperatures compared to those that were originally acclimatized to the warmer ones (Petropoulos et al, 2013;Petropoulos, 2015;Nozhevnikova et al, 2007). Culler et al (2015) also described a similar phenomenon in nature in which coldadapted mosquitoes avoid increased mortality from predators when in warmer climates by having faster metabolic rates resulting in faster growth-or in other words more efficient intestinal microflora. After acclimation the sludge concentration was increased by 100% and 350% (days 100 and 175, respectively) to promote treatment efficiency without limiting mass transfer.…”
Section: 4mentioning
confidence: 81%
“…Previous studies showed that acclimation to low temperatures forms microbial communities that are not only sturdier but also perform better when at warmer temperatures compared to those that were originally acclimatized to the warmer ones (Petropoulos et al, 2013;Petropoulos, 2015;Nozhevnikova et al, 2007). Culler et al (2015) also described a similar phenomenon in nature in which coldadapted mosquitoes avoid increased mortality from predators when in warmer climates by having faster metabolic rates resulting in faster growth-or in other words more efficient intestinal microflora. After acclimation the sludge concentration was increased by 100% and 350% (days 100 and 175, respectively) to promote treatment efficiency without limiting mass transfer.…”
Section: 4mentioning
confidence: 81%
“…The only mosquito species in our study area is Aedes nigripes Zett. Immature A. nigripes hatch from eggs and develop in shallow temporary ponds during May and June (Culler et al 2015). Immature A. nigripes hatch from eggs and develop in shallow temporary ponds during May and June (Culler et al 2015).…”
Section: Study Systemmentioning
confidence: 99%
“…Our previous study indicated immature survival probabilities ranging from 0.01 to 0.40 among ponds in 2011 and 2012 (Appendix S1: Table S2; Culler et al 2015). We varied probability(adult t+1 |egg) from 0 to 1 to account for variation in survival rates from the egg through the adult stage.…”
Section: Population Modelmentioning
confidence: 99%
“…The study of tundra arthropods in the context of rapid environmental change has indeed yielded insights into general patterns of ecological change Culler et al 2015). Tundra arthropods exhibit significant phenological responses to these changes (Høye and Forchhammer 2008;Tulp and Schekkerman 2008;Høye et al 2014).…”
Section: Introductionmentioning
confidence: 99%